242 The Importance of Frailty Assessment as a Mortality Indicator and Surgical Decision-Making Tool. (28th February 2022) - Cheng, Y.S.; Brown, K.; Harley, S.; Allen, C.; Nasr, H.; Rudzki, D.; Claridge, M.; Adam, D.; Juszczak, M.T.
Abstract: Background: Frailty is a multidimensional syndrome, which can lead to poorer health outcome. Frailty score is a proven reliable indicator of post-operative morbidity and mortality; however, its application in clinical practice is limited. Aim: The study aimed to assess the association between frailty marker and one- year mortality rate and explore its impact in clinical decision making in patients with abdominal aortic aneurysms. Method: Consecutive patients with abdominal, thoracic, and thoracoabdominal aortic aneurysms presented at dedicated aortic clinic between July 2019 and April 2020 were included. Markers for frailty and sarcopenia using Rockwood Clinical Frailty Scale, SARC-F questionnaire, morphometric analysis for sarcopenia, one-year mortality and fitness were recorded. Multi-disciplinary team (MDT) was blinded to frailty and sarcopenia data; surgical decisions made by MDT were recorded separately. Results: We assessed 83 patients (median age 75 [72, 82], 85% male; median aneurysm diameter 6cm [5.8, 7.0]. Sixteen patients were deemed frail, five patients had sarcopenia and thirty-one patients had myopenia. Seventeen patients were deemed not fit for surgery; 41% of these were frail compared with 14% out of those who were deemed fit. The odds ratio of being frail and unfit for surgery was 4.33 (95% CI 1.27–14.82, p = 0.010). Frailty was significantly associated with one-year mortality irrespective of fitness for surgery, sarcopenia and myopenia (OR 10.28, 95%CI 1.82–57.93, p = 0.009). SARC-F and myopenia was not associated with one-year mortality at (OR 1.66, 95%CI 0.03–19.25, p = 0.523) and (OR 0.59, 95%CI 0.09–2.85, p = 0.514), respectively. Conclusions: Frailty score was associated with both one-year mortality and fitness for surgery decision made by MDT.